Predatory thrips in action: Scolothrips sexmaculatus (Pergande) and Scolothrips tenuipennis zur Strassen, 1965 (Thripidae) feeding on Tetranychus urticae (Acari) in Brazil - Cavalleri, Adriano; Fernandez, Patricia Santos De Castro; Teixeira, Alexandre Jacintho; Souza, Thiago Sampaio De; Aguiar-Menezes, Elen De Lima (Zootaxa, 2025)
The purpose of this study is to report the presence in Brazil of two predatory thrips species feeding on mites in commercial hop plantations (Humulus lupulus, Cannabaceae). The mite, Tetranychus urticae Koch, is known as the two-spotted spider mite (TSSM) and is a major pest in several crops, including hop, threatening yields by damaging leaf tissues and, in severe cases, covering foliage with webs. It is native to Eurasia but is now present globally, with a wide range of natural enemies, including commercially used biological controls such as Stethorus beetles and phytoseiid mites (Sirrine et al. 2010; Turner et al. 2011).